Geographic Regions for Crop Cost-Return Budgets - Langemeier, Larry N. (My University, 1998)
This publication outlines the regional areas of Kansas for the crop cost-return guides.
MF2235_1998_10
Keywords: MF2235; Economics; Crops; MF